2020
DOI: 10.3389/fimmu.2020.01346
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Flexibility and Innate Immunity in Renal Ischemia Reperfusion Injury: The Fine Balance Between Adaptive Repair and Tissue Degeneration

Abstract: Renal ischemia reperfusion injury (IRI), a common event after renal transplantation, causes acute kidney injury (AKI), increases the risk of delayed graft function (DGF), primes the donor kidney for rejection, and contributes to the long-term risk of graft loss. In the last decade, epidemiological studies have linked even mild episodes of AKI to chronic kidney disease (CKD) progression, and innate immunity seems to play a crucial role. The ischemic insult triggers an acute inflammatory reaction that is elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 167 publications
(228 reference statements)
4
62
0
Order By: Relevance
“…Besides ROS and apoptosis, the metabolic disorder was identified as a new mechanism that leads to kidney function decline. The tubular epithelial cell, the most susceptible cell type to cisplatin in the kidney, combusts fatty acids to generate adenosine triphosphate (ATP) through oxidative phosphorylation for the high transport and reabsorption activities (Tammaro et al, 2020). Tran and colleagues recently showed that nicotinamide adenine dinucleotide (NAD + ), an essential cofactor for fatty acid oxidation (FAO) (Szeto, 2017), was decreased in the renal tubular cells with IRI treatment, and this reduction in NAD + may develop marked fat accumulation and renal function impairment (Tran et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Besides ROS and apoptosis, the metabolic disorder was identified as a new mechanism that leads to kidney function decline. The tubular epithelial cell, the most susceptible cell type to cisplatin in the kidney, combusts fatty acids to generate adenosine triphosphate (ATP) through oxidative phosphorylation for the high transport and reabsorption activities (Tammaro et al, 2020). Tran and colleagues recently showed that nicotinamide adenine dinucleotide (NAD + ), an essential cofactor for fatty acid oxidation (FAO) (Szeto, 2017), was decreased in the renal tubular cells with IRI treatment, and this reduction in NAD + may develop marked fat accumulation and renal function impairment (Tran et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid accumulation is clearly a common phenotype following renal injury; however, similar to the uncertainties regarding its damaging or beneficial effect, the underlying cause of this phenomenon also requires further study. As ischaemia is known to suppress OXPHOS [13], a major energy‐producing metabolic pathway in the kidney, it is plausible that pathways associated with lipid metabolism could also be affected by an ischaemic event. Our aim was to investigate the alterations in lipid profile and the underlying metabolic pathway rewiring that occurs during IRI.…”
Section: Introductionmentioning
confidence: 99%
“…Renal ischemia-reperfusion injury is a major risk factor affecting the prognosis of AKI and the functional recovery and long-term survival of grafts after renal transplantation ( 1 ). Innate and adaptive immune cells, such as macrophages, dendritic cells, neutrophils, and lymphocytes, are involved in the pathogenesis of renal injury after ischemia-reperfusion injury (IRI) ( 2 ).…”
Section: Introductionmentioning
confidence: 99%